Impact of Information Technology on Consumer Protection in the Digital Era - Mamta Saraswat (Integrated Journal for Research in Arts and Humanities, 2022)
Online shopping is one form of non-store patronage medium and the reason customers are moving towards online shopping is that they experience a lot of conveniences. For many housewives planning time, transportation time, and transportation expenses. The present study was conducted for a comparative study of online shopping among the working and non-working women in the urban area of the Agra district. The data were analyzed by using a t-test. Samples of 50 women (25 workings + 25 non-working) were taken from Agra, City. In this study statistically, significant differences regarding online shopping for whom and cost of online shopping were observed (p<0.05) between working and non-working women. Although no significant difference in buying practices of type clothes, beneficial, to facing problems between working and non-working women at 5% level of significance.